APPLICATIONS MULTIMEDIA PLAYER USING MICROSOFT VISUAL BASIC 6.0 - Maryoto Maryoto; Linda Wahyu Widianti, SKom, MMSI. (Jurnal Sistem Informasi, 2004)
In the background with the development of the technology world at the moment,there are various kinds of entertainment facilities, one Multimedia Player (MP-3). InMultimedia Player application can be understood how Microsoft Visual Basic 6.0 cancreate an application.In this study, the authors use one example of a visual programming language,Microsoft Visual Basic 6.0 that is very supportive in making the application.